IMAGE OF RUSSIA IN ENGLISH- SPEAKING TOURIST INTERNET DISCOURSE - M. G. Bolshakova (Современная наука и инновации, 2022)
This article presents an analysis of the image of Russia in the tourist Internet discourse and is devoted to the study of English-language tourist texts. The main purpose of the work is to study the lexical and stylistic features of English-language texts about Russia in the tourist Internet discourse. In the article, the author provides information about the features of the modern tourist Internet discourse, examines the distinctive features of the English-language tourist Internet discourse. As a result of the study, the most frequent lexico-stylistic features characteristic of the analyzed tourist Internet texts were identified.